1993
DOI: 10.1136/vr.132.13.317
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of long distance airborne transmission of Aujeszky's disease (pseudorabies) virus

Abstract: In spite of the eradication of Aujeszky's disease in Denmark a single outbreak was recorded in December 1988 and another severe epizootic took place during the winter and spring of 1989/90. The epizootic occurred in nearly the same areas as the preceding epizootic during the winter of 1987/88. Identification of the strains of virus involved eliminated the possibility that the latest epizootic was due to the persistence of virus in the pig population. Furthermore, as during the preceding epizootic, initial reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(59 citation statements)
references
References 0 publications
3
51
0
5
Order By: Relevance
“…Although the range in herd sizes (50-600 sows) was fairly small compared to other studies [18,46], we did find a positive association between herd size and ADV seroprevalence. This is consistent with results obtained by Anderson et al [2], Morrison et al [31] and Christensen et al [9], but it is in contrast with studies conducted by Weigel et al [46]. ADV is introduced more often in large herds because they usually have more frequent contacts outside the herd than small herds.…”
Section: Discussionsupporting
confidence: 92%
“…Although the range in herd sizes (50-600 sows) was fairly small compared to other studies [18,46], we did find a positive association between herd size and ADV seroprevalence. This is consistent with results obtained by Anderson et al [2], Morrison et al [31] and Christensen et al [9], but it is in contrast with studies conducted by Weigel et al [46]. ADV is introduced more often in large herds because they usually have more frequent contacts outside the herd than small herds.…”
Section: Discussionsupporting
confidence: 92%
“…Demonstration of higher frequency of latency in the sacral ganglia instead of the trigeminal ganglia of naturally and experimentally infected feral or hybrid swine is consistent with previous results that indicate that the main route of transmission of PRVs indigenous to feral swine is venereal (Romero et al, , 2001 and not respiratory as is the case of PRV strains in domestic swine (McFerran and Dow, 1964;Christensen et al, 1993). An example of a herpesvirus primarily transmitted venereally is herpes simplex virus 2 (HSV-2), the cause of genital herpes in humans in which latency has been shown to occur mainly in the sacral dorsal root (S2-S4) ganglia (Aurelian, 1989).…”
Section: Discussionsupporting
confidence: 88%
“…Transmission of PRV in domestic swine usually occurs by the oropharyngeal route after direct contact of infected and susceptible animals and the ingestion or aspiration of infected aerosols, secretions, and excretions (McFerran and Dow, 1964;Christensen et al, 1993). Recently, we reported that transmission of PRVs indigenous to feral swine occurs mainly by the genital route during the mating of PRVinfected feral swine to susceptible feral or domestic swine (Romero et al, , 2001.…”
Section: Introductionmentioning
confidence: 99%
“…2 Airborne transmission is a possibility. 8,34 However, the closest genetic relationship between the C2a-D1a (both dogs) and D1b-A1-A2 (swine and sheep) subclusters was between the isolates from farm D1, implicating transmission between the dog and swine on that farm. A similar pattern of canine transmission may have been involved in the spread of ADV from D1 to A1 and A2.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,24,26,38 Restriction fragment length polymorphism (RFLP) among viral isolates has been used to distinguish field and vaccine strains of ADV. 11,12,19,29 To utilize REA for epidemiologic purposes, it was necessary to establish that ADV is relatively stable genetically, both in vivo and in vitro.…”
mentioning
confidence: 99%